Curvature suppresses the Rayleigh-Taylor instability - Trinh, Philippe H.; Kim, Hyoungsoo; Hammoud, Naima; Howell, Peter D.; Chapman, S. Jonathan; Stone, Howard A. (Physics of fluids (1994), 2014)
The dynamics of a thin liquid film on the underside of a curved cylindrical substrate is studied. The evolution of the liquid layer is investigated as the film thickness and the radius of curvature of the substrate are varied. A dimensionless parameter (a modified Bond number) that incorporates both geometric parameters, gravity, and surface tension is identified, and allows the observations to be classified according to three different flow regimes: stable films, films with transient growth of perturbations followed by decay, and unstable films. Experiments and linear stability theory confirm that below a critical value of the Bond number curvature of the substrate suppresses the Rayleigh-Taylor instability.